Is Instagram Effective for Reproductive Health Promotion in Adolescents during the COVID-19 Pandemic? - Mediastuti, Fitriani; Revika, Era (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: The majority of teens have smartphones and are involved with digital media. Almost 45% of teens described being online "almost constantly." During the COVID-19 pandemic, access to learning reproductive health directly in schools is very limited. Various risks posed by the COVID-19 outbreak have an impact on changes in the new order of life. Teenagers learn more from home. Many teenagers use social media and the internet to learn about reproductive health. Objective: The purpose of this study was to determine the effectiveness of reproductive health promotion through Instagram during the COVID-19 Pandemic. Methods: An analytic observational study with a cross-sectional approach was conducted among 31 respondents from December 2021 to July 2022. The sample was all who are followers of PIKM Larashati Instagram and ready to be a respondent. The sampling technique was taken by accidental sampling. Data collection was carried out using Google Forms. Data were analyzed with both univariate and bivariate analysis. Results: The findings in this study indicate that adolescents who are followers of PIKM Larashati Instagram have good knowledge about adolescent reproductive health as much as 58.07%. This study also states that the positive attitude of adolescents who are followers of the Larashati PIKM Instagram toward reproductive health is 61.29%. It was found that there was no relationship between the knowledge and attitudes of adolescents because the value of sig = 0.072 which means it is greater than 0.05. Conclusion: Promotion of reproductive health through Instagram by PIKM Larashati regarding reproductive health during the COVID-19 Pandemic is effective for adolescents and adolescents are recommended to follow accounts containing health education.